Directing film techniques and aesthetics - Rabiger, Michael (Focal Press, 2013)
This comprehensive manual has inspired tens of thousands of readers worldwide to realize their artistic vision and produce well-constructed films. Filled with practical advice on every stage of production, this is the book you will return to throughout your career.?Directing covers the methods, technologies, thought processes, and judgments that a director must use throughout the fascinating process of making a film. The core of the book is the human, psychological, and technical knowledge that every director needs, the enduring elements of the craft that remain vital.